Age at start of using tobacco on the risk of head and neck cancer: pooled analysis in the International Head and Neck Cancer Epidemiology Consortium (INHANCE) - Chang, Chun-Pin; Chuang, Shu-Chun; Berthiller, Julien; Wünsch, Victor; Levi, Fabio; Dal Maso, Luigino; Smith, Elaine; Ramroth, Heribert; Boccia, Stefania; Brenner, Hermann; Boffetta, Paolo (Cancer epidemiology, 2019)
Background - Tobacco use is a well-established risk factor for head and neck cancer (HNC). However, less is known about the potential impact of exposure to tobacco at an early age on HNC risk. - Methods - We analyzed individual-level data on ever tobacco smokers from 27 case-control studies (17,146 HNC cases and 17,449 controls) in the International Head and Neck Cancer Epidemiology (INHANCE) consortium. Adjusted odds ratios (ORs) and 95% confidence intervals (CIs) were estimated using random-effects logistic regression models. - Results - Without adjusting for tobacco packyears, we observed that younger age at starting tobacco use was associated with an increased HNC risk for ever smokers (OR<10 years vs. ≥30 years: 1.64, 95% CI: 1.35, 1.97). However, the observed association between age at starting tobacco use and HNC risk became null after adjusting for tobacco packyears (OR<10 years vs. ≥30 years: 0.97, 95% CI: 0.80, 1.19). In the stratified analyses on HNC subsites by tobacco packyears or years since quitting, no difference in the association between age at start and HNC risk was observed. - Conclusions - Results from this pooled analysis suggest that increased HNC risks observed with earlier age at starting tobacco smoking are largely due to longer duration and higher cumulative tobacco exposures.